PASANG SURUT DOMINASI ISLAM TERHADAP KESENIAN REOG PONOROGO - Achmadi, Asmoro (Analisis: Jurnal Studi Keislaman, 2013)
Ponorogo is well-known as “Bumi Reog” by its reog, but it’s also famous as the city of students by Gontor Modern Pesantren. And as the ancient  city, Ponorogo surely has its local wisdom (local genius) rooted in their religious values and value of reog art. This article aims to deliberate which one of them is more dominant in its existence  as Ponorogo society’s  local wisdom (local genius). Here, the writer use the Max Scheler’ s theory of the value that argues that in the values there is a hierarchy in the value namely: religion  values (the  highest  level), spiritual  values,  life values, and pleasure values (the lowest level). Benchmark value of Max Scheler resulted, that religion values (Islam) contains spiritual values get the highest  place compared  with  the culture  values. Spiritual values include the values of: religious proselytizing [dakwah], sustainability, trust, and magical. While cultural values include the values of: culture,  beauty,  moral, artistic,  symbolic, superiority, heroism, justice, welfare, entertainment, satisfaction, competitive,  material, and performances.